Effects of different drying temperatures on the content of phenolic compounds and carotenoids in quinoa seeds (Chenopodium quinoa) from Finland - Salvatore Multari; Alexis Marsol-Vall; Marjo Keskitalo; Baoru Yang; Jukka-Pekka Suomela (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
This investigation studied the effects of different drying temperatures on the content of phenolic compounds and carotenoids in quinoa seeds (Chenopodium quinoa) from Finland. Five drying temperatures were applied to reach a dry matter content of 94–95% w/w: room temperature, 40, 50, 60, and 70 °C. The process performed at 70 °C allowed the greatest recovery of total phenolic compounds, 994 ± 28 mg kg−1. Ferulic acid and quercetin were the main phenolics identified. The drying process performed at 60 °C allowed the greatest recovery of cumulative carotenoids, 2.39 ± 0.05 mg kg−1. The carotenoids identified were xanthophylls, e.g., lutein, zeaxanthin and neochrome. The use of heat impacted positively on the phytochemical composition of quinoa. The concentration of phenolics and carotenoids increased steadily with the rise in drying temperature. Results obtained provide scientific knowledge that can be used by producers to increase the availability of such phytochemicals in quinoa seeds.